2021
DOI: 10.1002/smll.202104681
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Stacked Photocatalyst Design Enables Spatially Separated Ni(OH)2 Redox Cocatalysts for Overall CO2 Reduction and H2O Oxidation

Abstract: Construction of photocatalytic systems with spatially separated dual cocatalysts is considered as a promising route to modulate charge separation/transfer, promote surface redox reactivities, and prevent unwanted reverse reactions. However, past efforts on the loading of spatially separated double‐cocatalysts are limited to hollow structured semiconductors with inner/outer surface and monocrystalline semiconductors with different exposed facets. To overcome this limitation, herein, enabled by a unique stacked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Such differentiated deposition sites of Pt and MnO x further confirm that the C/CdS@ZnIn 2 S 4 follows the Type-II charge transfer path rather than the direct Zscheme mechanism. 39 Taking the architecture of C/CdS@ZnIn 2 S 4 into consideration, a possible mechanism for the photocatalytic CO 2 reduction has been proposed. As illustrated in Figure 6e, the narrow-bandgap CdS core and the ZnIn 2 S 4 shell rather than the zero-bandgap carbon supporter are excited to generate photo-induced electrons and holes under visible light illumination.…”
Section: Photocatalytic Mechanism Analysismentioning
confidence: 99%
“…Such differentiated deposition sites of Pt and MnO x further confirm that the C/CdS@ZnIn 2 S 4 follows the Type-II charge transfer path rather than the direct Zscheme mechanism. 39 Taking the architecture of C/CdS@ZnIn 2 S 4 into consideration, a possible mechanism for the photocatalytic CO 2 reduction has been proposed. As illustrated in Figure 6e, the narrow-bandgap CdS core and the ZnIn 2 S 4 shell rather than the zero-bandgap carbon supporter are excited to generate photo-induced electrons and holes under visible light illumination.…”
Section: Photocatalytic Mechanism Analysismentioning
confidence: 99%
“…Besides, as revealed by linear sweep voltammetry curves (Figure S17, Supporting Information), in contrast to Au loading, MoS 2 coating introduces more active sites for CO 2 reduction and H 2 O oxidation, benefiting the occurrence of overall redox reaction on the TiO 2 /Au@MoS 2 . [62,63] Previous researches have shown that MoS 2 is an efficient catalyst for O 2 evolution owing to its high hole mobility and powerful photo-oxidation ability. [64,65] When TiO 2 @MoS 2 /Au is taken into consideration, in addition to the sluggish consumption of electrons confined in TiO 2 core, the TiO 2 → MoS 2 hole migration and Au → MoS 2 hot electron injection accelerate the charge recombination in the MoS 2 interlayer (Figure S18, Supporting Information).…”
Section: Energy Band Alignments and Charge Transfer Pathway Analysismentioning
confidence: 99%
“…Further H 2 18 O isotopic labeling experiment is also conducted, and the signal at m/z = 36 corresponding to 18 O 2 is detected by gas chromatography/mass spectrometry measurement, unequivocally verifying the fact that the evolved O 2 actually originates from H 2 O oxidation (Figure S8b). 55…”
Section: Preparation and Characterizations Of Pbtio 3 -Based Catalystsmentioning
confidence: 99%